Rare case report: non-mass invasive ductal carcinoma presenting with rectal and cervical lymph node metastasis as the initial symptom - Qiong Zhang; Zhifeng Xiong; Yuan Gao; Min Zeng; Huachao Yang; Gang Lyu (Frontiers in Oncology)
It is uncommon for breast cancer to present with distant metastasis as the initial symptom. This study reported a 67-year-old female patient with breast non-mass invasive ductal carcinoma, who sought medical attention due to abdominal distention, lower abdominal pain, constipation, hematochezia, and left-sided neck swelling. After a thorough examination, pathology confirmed the diagnosis of breast invasive ductal carcinoma, along with cervical lymph node and rectal metastasis. The non-specific breast symptoms in this case posed challenges for the early diagnosis of breast cancer. This also suggests that for breast cancer patients without a history of gastrointestinal disease, the presence of changes in bowel habits should raise suspicion for metastatic lesions. Imaging combined with biopsy pathology plays an important role in the diagnosis and treatment of non-mass breast cancer. This case also underscores the importance of breast health awareness and routine breast cancer screening among women, both for clinical practice and public health initiatives. Notably, early identification and diagnosis of non-mass breast cancer, coupled with the development of personalized treatment plans through multidisciplinary collaboration, are essential for enhancing treatment efficacy.